The East Anglian Railways Company: a study in railway and financial history - Gordon, Donald Ian (1964)
This work covers the period from 1844 to 1862, and is set, against a national background, in the King's Lynn area, then suffering a time of severe economic transition as distant railways undermined the town's commercial monopoly, and low corn prices the agricultural economy. The companies, authorised in 1845 and amalgamating as the East Anglian Railways in 1847, were founded in a complex of personal greed, parochial ambition and commercial fears. In the following years they had to learn that they could not be the arbiters of the local economy. Misguided directors, faulty estimates, defective accounts, the inadequacies of Parliament, the duplicity of the Eastern Counties Railway and other factors led to bankruptcy. Slow recovery and appreciation of the company's proper place in the economy were complicated by the key role which the East Anglian assumed in the conflict between the Eastern Counties and Great Northern railways, the effects of which proved most serious to the local economy.